Half-Heusler based multicomponent alloys for high temperature thermoelectric applications - Mishra, Soumya Ranjan (Nanyang Technological University, 2023)
The efficiency of thermal-to-electrical conversion depends on high electrical conductivity (σ), high Seebeck coefficient (S=ΔV⁄ΔT), and low thermal conductivity (κ). Radioisotope thermoelectric generators in spacecraft require high-temperature thermoelectric materials like oxides, SiGe, and half-Heusler (HH) alloys. HH alloys with MgAgAs crystal structure, despite excellent electrical and mechanical properties, have high κ and need long annealing times. Traditionally, nanostructuring and mass defects have been employed to lower κ. Recently, high entropy materials have been explored to lower κ through lattice scattering. Higher configurational entropy in multicomponent HH Ti2NiCoSnSb helped obtain a single phase without annealing. The effect of nanostructuring in Ti2NiCoSnSb was studied by mechanical alloying and by milling the crushed powders of vacuum arc melted samples. While nanostructuring has helped lower the κ to 3.5 W/mK at room temperature, the S value was considerably reduced. Lowering the Ti content and increasing the Ni and Co content led to the precipitation of intermetallic Ni3Sn2 and full-Heusler Ni2TiSn secondary phases, respectively. The intermetallic phase improved the electrical conductivity and lowered κl at the expense of the S value in the Ti2-xNiCoSnSb samples. In the Ti2(NiCo)1+xSnSb alloys, the power factor increased till optimum doping of 2.5% Ni and Co due to the full-Heusler (FH) phase and thermal conductivity lowered till optimum doping of 5% Ni and Co due to phonon scattering at HH/FH interfaces. The effect of doping was understood through the introduction of lighter element Al and heavier elements Zr and Ta, respectively. Based on the structure-property optimizations, compositional tuning by multi-element doping was performed. A thermoelectric figure of merit of 0.692 was observed in Ti1.6Al0.2Ta0.2NiCoSn0.5Sb1.5 double half-Heusler alloy at 823 K. The precipitating AlCoNiTa type FH phase helped increase the power factor and lower thermal conductivity by scattering phonons at the HH/FH interface in these alloys. Nb2FeCoSnSb double half-Heusler exhibited ZT closer to Ti2NiCoSnSb. The effect of Sb content in Ti2NiCoSnSb-based alloys has been extensively studied (Karati et al., 2020, 2022b). For comparison, the effect of the processing route and Sb content on thermoelectric properties was studied in Nb2FeCoSnSb. The impact of varying Fe and Co content on the thermoelectric properties was also studied. First-principles calculations helped us understand the phase evolution and resultant electronic band structures in these alloys.